2004
DOI: 10.1108/02621710410549576
|View full text |Cite
|
Sign up to set email alerts
|

Optimising skills transfer via outdoor management development

Abstract: A framework for the optimum development and transfer of conflict-handling skills via outdoor management development (OMD) programmes has already been presented (Part I, Journal of Management Development, Vol. 23 No. 7). A qualitative study with ten OMD providers confirmed the framework to be tenable insofar as the concepts represented within it were reportedly utilised as aspects of provision but, crucially, there was little evidence of an underlying rationale or set of principles to optimise effect. Hence, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Notably, the results of this study also strongly suggested that the program caused a reduction in employee sick days and improvements in quality improvement results-that is, positive outcomes at the organizational level (Kirkpatrick, 1996). An investigation of participants' perceptions of efficacy of different OMD approaches for transfer of learning to the workplace (Burke & Collins, 2004) also suggests some degree of retention and/or use of learning.…”
Section: Professional Development and Adventure Educationmentioning
confidence: 99%
“…Notably, the results of this study also strongly suggested that the program caused a reduction in employee sick days and improvements in quality improvement results-that is, positive outcomes at the organizational level (Kirkpatrick, 1996). An investigation of participants' perceptions of efficacy of different OMD approaches for transfer of learning to the workplace (Burke & Collins, 2004) also suggests some degree of retention and/or use of learning.…”
Section: Professional Development and Adventure Educationmentioning
confidence: 99%
“…OMD research often focuses upon training outcomes and neglects the underlying mechanisms by which these effects are elicited (Burke and Collins, 2004a, p. 678). According to Hodgkinson such ‘A‐theoretical empirical studies, however well executed, do not typically yield enduring contributions to the academic enterprise or policy and practice' (2005, p. 2).…”
Section: Introductionmentioning
confidence: 99%
“…As conceptual frameworks have been developed, a number of studies have taken a positivist, confirmatory approach to OMD: testing hypotheses generated through extensive analyses of the literature (Burke and Collins, 2004b; Hamilton and Cooper, 2001; Ibbetson and Newell, 1996; Keller and Olson, 2000; Lucas, 1992; Mazany, Francis and Sumich, 1995; Ng, 2001). These have often produced equivocal results and have generally failed to support the predicted relationships, indicating that our theoretical understanding of OMD may be insufficient to support methodological approaches such as these.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, business, sports teams, children and the military have all been the focus of programmes designed to develop skills that will transfer to the 'home' environment. However, the transfer of learning becomes a tacit assumption far too often in these settings, and several authors (for example, Brown, 2010;Burke & Collins, 2004a, 2004b have stressed the need for explicit consideration. Consider the following quote from Wolfe and Samdahl about the use of 'high ropes' challenge courses:…”
Section: Applying Learning In 'Real' Lifementioning
confidence: 99%